Culturas bioenérgéticas: produção de biomassa, decomposição e liberação de nitrogênio dos resíduos culturais - Simon, Juciéli (2009)
The searching of renewable energy sources is growing the interest in the biofuels obtaining from vegetable oils, and stand out crop as sunflower, soy and castor bean. Besides the production of raw material to obtaining of renewable energy, those cultures accumulate in the biomass the carbon that can be incorporate to the organic matter in the soil during the crop residue decomposition. A field experiment was carried out on a typic Hapludalf in an experimental area of the Universidade Federal de Santa Maria, Santa Maria, state of Rio Grande do Sul, in the agricultural year of 2006/07. The aim was to evaluate the biomass production, decomposition and nitrogen release of crop residue of the bioenergy crop. The treatments were: T1 - Sunflower (Helianthus annus L., var. AGUARÁ-3); T2 - Soy (Glycine max L.); T3 Hybrid of the castor beans (Ricinus communis L. var. Lira); T4 - Variety of the castor beans (Ricinus communis L. var. AL Guarany 2002). It was evaluated de dry matter and carbon accumulated, decomposition and nitrogen release of the crop residues and grain yield were evaluated. In the castor beans, 41% of C accumulated in the aerial part during the cycle of the culture are in the leaves, being the quantification of that compartment of essential biomass to evaluate the contribution of the castor beans for the contribution of C soil. The soy crop residues presented lower decomposition and nitrogen release. The soy crop, for to produce raw material to biodiesel production and to add high amounts of C in the soil, without the need of N application, it shows high potential for the mitigation of the greenhouse effect among the bioenergy crop evaluated.